Immunological Alterations in Haemophiliacs Treated with Lyophilized Factor VIII Cryoprecipitate from Volunteer Donors - Ceuppens, J L; Vermylen, J D; Colaert, J; Desmyter, J; Gautama, K; Stevens, E; The, A L; Vanham, G; Vermylen, C; Verstraete, M (Thrombosis and Haemostasis, 1984)
We studied immune function in Belgian haemophiliacs treated with Factor VIII from volunteer donors. No patient had clinical evidence of immune deficiency. We found a decrease in T-helper cells (p <0.0005), in the ratio of T-helper over T-cytotoxic/ suppressor cells (1.72 ± 0.47 versus 2.24 ± 0.82 in controls, p <0.005) and in lymphocyte responsiveness to mitogens (p <0.05).These findings could not be linked to the amount of F VIII received over the last year, the time since last F VIII administration, circulating immune complexes (54% positive patients, 7% positive controls, p <0.005), increased ALT levels, antibodies to cytomegalo-virus (85% of the patients, 45% of the controls, p <0.005), antibodies to Epstein-Barr virus, nor to the presence of HLA-DR 5 which was found in 56% of the haemophiliacs (20% of the overall Belgian population, p <0.005).Either F VIII induces long lasting immunological alterations unrelated to AIDS, or haemophilia is itself associated with such changes.
Keywords: Haemophilia; Acquired immune deficiency syndrome; Factor VIII; T cell subsets; Immune complexes